2010
DOI: 10.1029/2009jc005587
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami damage reduction performance of a mangrove forest in Banda Aceh, Indonesia inferred from field data and a numerical model

Abstract: [1] Since the 26 December 2004 Indian Ocean tsunami, the role of mangrove forests as natural defenses protecting coastal communities from tsunami disaster has been highlighted. However, some mangrove forests were destroyed by that tsunami. They are expected to have lost their protective functions. In this study, we develop a fragility function to assess the mangrove trees' vulnerability, expressed as the damage probability of mangrove trees, based on field surveys and numerical modeling of the 2004 Indian Ocea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(29 citation statements)
references
References 30 publications
1
25
0
3
Order By: Relevance
“…Based on field observations, experienced damage, and satellite images of the last tsunami events, some reports have apparently shown significant role of coastal forest in reducing the impact of tsunamis 2,3 . Others supported those findings based on semi-analytical and empirical approaches through experiments with both physical and numerical models 4,5,6,7 . The 2011 Japan Tsunami, however, have provided us completely different facts where many coastal forest were completely destroyed by the extreme tsunami.…”
Section: Introductionsupporting
confidence: 58%
“…Based on field observations, experienced damage, and satellite images of the last tsunami events, some reports have apparently shown significant role of coastal forest in reducing the impact of tsunamis 2,3 . Others supported those findings based on semi-analytical and empirical approaches through experiments with both physical and numerical models 4,5,6,7 . The 2011 Japan Tsunami, however, have provided us completely different facts where many coastal forest were completely destroyed by the extreme tsunami.…”
Section: Introductionsupporting
confidence: 58%
“…However, the extent to which mangroves can reduce the damage caused by a tsunami or storm surge is much debated. Some scholars found that mangroves play a key role in protecting human lives and other resources by attenuating large waves and wind energy (e.g., Danielsen et al., ; Das & Vincent, ; Yanagisawa et al., ). During the Indian Ocean tsunami in 2004, for instance, no lives were lost in the hamlets on the Indian Tamil Nadu coast, which were protected by dense or shrubby mangroves (Kathiresan & Rajendran, ).…”
Section: Discussionmentioning
confidence: 99%
“…The country is prone to cyclones, floods, landslides, earthquakes, and drought. Mangroves play an important role in providing protection against these natural disasters (Yanagisawa, Koshimura, Goto, Miyagi, & Imamura, 2010;Yanagisawa et al, 2009). For example, the Meinmahla Kyun Wildlife Sanctuary saved thousands of people that relied on marine resources in the Ayeyarwady Delta during the deadly 2008 Cyclone Nargis (Aung & MacDonnell, 2016).…”
Section: Environmental and Social Impacts Of Mangrove Forest Cover mentioning
confidence: 99%
“…Rhizophoraceae, such as Rhizophora apiculata, R. mucronata and R. stylosa are found high resiliency after the tsunami disturbance as well as Nypa fruticans and Sonneratia caseolaris. According to some publication [35][36][37][38][39] , the species have also high level of persistent and resilient in other sites where they were affected by tsunami. Cochard et al 40 stated that the resilience of a mangrove ecosystem is likely to be influenced by factors such rates of tree regeneration and seedling recruitment, and renewed sedimentation reversing soil losses during the hazardous event.…”
Section: Discussionmentioning
confidence: 99%